3 monkeys - Richards, Emily; Dohrn, Martin; Fox, Mark (London, Sydney : BBC de Londres, 1998)
Sumario: Muestra especies de monos que viven en el área de Santa Elena, Costa Rica. Presenta hábitos, vida social.
Keywords: MONOS -- COSTA RICA